Ronnie Po-chia HSIA, Matteo Ricci and the Catholic Mission to China, 1583- -1610: A Short History with Documents. Indianapolis, Hackett Publishing Company, Inc., 2016 (Passages: Key Moments in History). - Danieluk, Robert (Annales Missiologici Posnanienses, 2019)
.